2018
DOI: 10.1109/twc.2018.2846222
|View full text |Cite
|
Sign up to set email alerts
|

Energy- and Spectral-Efficient Adaptive Forwarding Strategy for Multi-Hop Device-to-Device Communications Overlaying Cellular Networks

Abstract: Abstract-Device-to-device (D2D) communications in cellular networks enable direct transmissions between user equipments (UEs). If the source UE (SUE) and the destination UE (DUE) are far away from each other or the channel between them is too weak for direct transmission, then multi-hop D2D communications, where relay UEs (RUEs) forward the SUE's data packets to the DUE, can be used. In this paper, we propose an energyefficient optimal adaptive forwarding strategy (OAFS) for multihop D2D communications. OAFS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…[35] Proposes energy efficient GA to reduce the delay constrained multicast tree maximize the life of network. Similarly, authors also gave importance to energy efficiency during search of optimal route from SE to RUE to DE in [41]; they propose (OAFS) that is optimal adaptive forwarding strategy for multi-hop D2D communications and to reduce the computational complexity uses sub-optimal adaptive forwarding strategy (SAFS).…”
Section: Related Workmentioning
confidence: 99%
“…[35] Proposes energy efficient GA to reduce the delay constrained multicast tree maximize the life of network. Similarly, authors also gave importance to energy efficiency during search of optimal route from SE to RUE to DE in [41]; they propose (OAFS) that is optimal adaptive forwarding strategy for multi-hop D2D communications and to reduce the computational complexity uses sub-optimal adaptive forwarding strategy (SAFS).…”
Section: Related Workmentioning
confidence: 99%
“…where U D2D mn is the utility of DT n as shown in Equation (12). The first constraint guarantees that DT n is willing to cooperate.…”
Section: Dt N 'S Strategy In Stage I Imentioning
confidence: 99%
“…In order to maximizing the utility given by Equation 11, EU m intends to share its spectrum resource with a best D2D transmission pair (DT n , DR n ). On the other hand, a D2D transmission pair (DT n , DR n ) intends to provide cooperative assistance for an appropriate EU in order to win a transmission opportunity within the licensed band for its own traffic, while simultaneously maximizing its utility formulated by Equation (12). Hence, based on the matching theory, both the EUs and the DTs in our system are considered as a pair of disjoint sets.…”
Section: Matching Game For Eus and D2d Pairsmentioning
confidence: 99%
“…Optimal rate allocation scheme has been proposed in [17], and it found that system's error-free SET can be achieved. Energy-and-spectralefficient adaptive forwarding strategy for multi-hop device-to-device communications overlaying cellular networks has been proposed in [18], and it found that the higher EE and SE can be achieved.…”
Section: Introductionmentioning
confidence: 99%